Individualism–Collectivism, Private Benefits of Control, and Earnings Management: A Cross-Culture Comparison - Zhang, Xu; Liang, Xing; Sun, Hongyan (2013)
Using private benefits of control and earnings management data from 41 countries and regions, we provide strong evidence that cultures, together with legal rules and law enforcement, play a critical role in shaping corporate behavior. More specifically, we find that private benefits of control are larger and earnings management is more severe in collectivist as opposed to individualist cultures, consistent with the argument that agency problems between corporate insiders and outside investors are severe in collectivist culture. These results are robust to the inclusion of controls for country wealth, economic heterogeneity across countries, and international differences in ownership concentration.
Keywords: Moral Behavior; Corporate Governance; Earnings management; Private benefits of control; Collectivism; Individualism